1973
DOI: 10.1017/s0022172400046180
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to streptococcal opacity factor in human sera

Abstract: SUMMARYTwo tests are described for detecting antibody to the type-specific opacity factor (OF) of group A streptococci. This antibody was detected among patients convalescent from streptococcal sore throat in two communities in which outbreaks due to opacity factor-producing strains of group A streptococci occurred.In an outbreak due to streptococci of M-type 22 there was a close correspondence between the distribution of anti-OF and of bactericidal M-antibody for the type. In a smaller outbreak due to M-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…None of the sera tested contained antibodies to OF from M-types 60 or 62. Within the population studied, antibodies to OF from M-type 25 were commonest (25), followed by types 4 (19), 22 (18), 2 (1 1), 9 and 48 (10 each), 49 (8) and 28,61,75 (three each) (table V). …”
Section: Resultsmentioning
confidence: 96%
“…None of the sera tested contained antibodies to OF from M-types 60 or 62. Within the population studied, antibodies to OF from M-type 25 were commonest (25), followed by types 4 (19), 22 (18), 2 (1 1), 9 and 48 (10 each), 49 (8) and 28,61,75 (three each) (table V). …”
Section: Resultsmentioning
confidence: 96%
“…The OF-neutralization test was performed in one of two ways: (1) by incorporating a hot-acid extract orbroth supernatant ofan OF-positive streptococcus, together with horse serum, in agar gel, pouring this as a thin layer on a large glass slide, and placing loopfuls of antiserum on the surface (Maxted et al 1973b); a circular area of clearing of opacity was a positive reaction; or (2) by incorporating an anti-OF antiserum and horse serum in the agar, and placing loopfuls of culture extract or supernatant on the surface (Maxted et al 1973a) (Maxted et al 1973a) was used to detect 'bactericidal' M antibody in the sera of human subjects. RESULTS …”
Section: Typing Of 8treptococcimentioning
confidence: 99%
“…Anti-OF sera were either (1) stock M antisera that had been found to have opacity neutralizing activity against streptococci of corresponding M type, (2) rabbit antisera prepared specifically for the opacity-neutralization test (Maxted et al 1973b), (3) pooled antisera prepared by intraperitoneal inoculation of streptococci into guinea-pigs (Maxted, unpublished), or human sera found to have typespecific opacity-neutralizing activity (Maxted et al 1973a).…”
mentioning
confidence: 99%
“…OF antibody was not detected in more than half of all the M-antisera prepared for OF-positive serotypes. However, investigation of the time-course of antibody formation indicated that when anti-OF was formed it was often detected before antibodies to the M protein (Maxted, Widdowson and Fraser, 1974). Some sera contained M antibody but no OF antibody at the same stage of immunisation and others contained antibody to M and to OF antigens simultaneously.…”
Section: Discussionmentioning
confidence: 99%